Tawhidic paradigm and organizational policy and strategy practices - Mhd. Sarif, Suhaimi (KLibel, 2014)
This study explores the practice of Tawhidic Paradigm in organizational policy and strategy of small and medium enterprises (SMEs) in Malaysia. Tawhidic paradigm (TP) is an understanding to perform deeds in line with faith (‘aqīdāh), worship (‘ibādāh), and ethics (akhlāq) in the life as servant and vicegerent of Allah. In everyday life, one has to earn good value, which is compounded into the value of life as servant and vicegerent of Allah, enhances value in life, bottom line in the worldly and the Hereafter. TP is a guideline that based on Shari’ah, Islamic ethics and teaching principles for managing companies in the contemporary age. The TP is an addition to the existing standards and guidelines that produced by various agencies in Malaysia. The rigorous, comprehensive, and complete nature of TP contributes to beyond triple bottom line concerns of today’s companies for the sake of sustainability. This study uses personal interview with entrepreneurs of selected enterprises of SMEs in Malaysia. The entrepreneurs argued that they practiced TP according to teachings of Islam in terms of sincere, honest, truthful, and always abide by the teachings of Islam. Yet, they are still facing severe challenges to sustain their enterprises. However, they have strong dependency in Allah, and always reminding themselves to work hard as it is part of worshipping Allah. TP in OPS could bring significant practical implications in strategic management in enhancing efficiency, effectiveness, and sustainability of the companies. In conclusion, while the aware of TP in OPS significant theoretically, but in practice it has to be proven due to no such practices.